Penggunaan Media Telepon Mainan Untuk Meningkatkan Prestasi Belajar IPA - Amalia Nur Anifah; Maryono, Maryono; Firdaus, Firdaus (Institut Agama Islam Daruttaqwa Gresik, 2023)
Science learning, especially sound energy material, is not yet optimal, therefore it is necessary to take action to improve the quality of learning. with quality learning, the learning achievement of students will increase. This article aims to find out how to improve learning achievement and the implementation of learning by using toy telephone learning media. With the existence of learning, media can help students understand the material. Learning media when helping the learning process. The research method used is Classroom Action Research which is carried out with pra-siklus, cycle I, and cycle II. In this study, data collection was obtained using the test method to determine the increase in learning achievement, as well as non-test in the form of observation to determine the implementation of learning. The pre-cycle is carried out to find out how the students were before the action. While cycle I and Cycle II aim to find out the increase in learning achievement after the action. The learning media used in this study is a toy telephone which aims to help students understand the material during the learning process.